Butterfly buddies - Cox, Judy; Sims, Blanche (New York : Holiday House, 2001)
Third grader Robin has a series of mishaps and learns the value of honesty as she tries to become best friends with Zoey, her partner for a class project on raising butterflies. Includes butterfly care tips
Keywords: Schools -- Fiction; Honesty -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Butterflies -- Fiction